2022
DOI: 10.4028/www.scientific.net/jera.58.183
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Replacement of Granite Modified with Ife Iron and Steel Slag on Strength Properties of Concrete

Abstract: Steel is produced from iron ore and purification of metal scrap, leading to manufacture of hundreds of tonnes of steel slag each year. This study investigated the optimum replacement of granite with Ife Iron and Steel Nigeria Limited (ISN) slag that produce maximum Compressive Strength (CS), Split Tensile Strength (STS) and Flexural Strength (FS) of concrete using Response Surface Methodology (RSM) from Design Expert Version 7.0. The outcome of the study showed that the optimum replacement of granite with ISN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This is an indication that the strength and density of the soil can be enhanced with the addition of steel slag. This is because steel slag exhibited strong binding medium between the micro-sized clay particles leading to the formation of macro-sized particle of higher density and compactness which is primarily due to the high pozzolanicity as a result of high iron oxide content in steel slag [14,47].…”
Section: Compactionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an indication that the strength and density of the soil can be enhanced with the addition of steel slag. This is because steel slag exhibited strong binding medium between the micro-sized clay particles leading to the formation of macro-sized particle of higher density and compactness which is primarily due to the high pozzolanicity as a result of high iron oxide content in steel slag [14,47].…”
Section: Compactionmentioning
confidence: 99%
“…Studies have also clearly shown that not more than 50% of these wastes are currently converted into different purposes while larger percentages are dumped in the environment [9][10][11][12][13]. However, a sustainable and environmentally friendly way of solving these challenges is to consider the possibility of waste minimization by recycling and reusing [14][15], and one of such ways that has received the attention of environmental researchers, considered in this study, is by incorporating the industrial waste steel slag into the weak lateritic soil as a means of improving the properties of the soil and at the same time reducing the accumulation of the waste material in the environment. As the continuous production of wastes without proper disposal system will always pose a great threat to the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation